Comunidades mediadas pela internet: fatores de sucesso e modelo de ciclo de vida - Isoni, Miguel Maurício [UNESP] (Universidade Estadual Paulista (Unesp), 2009)
The current study is a descriptive and analytical research which aimed at studying the phenomenon of social network building which takes place in cyberspace, in order to comprehend its fundamentals in IMCs (Internet-Mediated Communities). This way, we wanted to identify the reasons of success and describe the life cycle of such communities. The research general goal was that of identifying the participation and attraction factors for IMC members, throughout their life cycle, whereas its specific goals were: to discriminate IMC defining attributes and success attributes; to discuss association and participation as IMC Success Factors (SF); to describe the SF’s nature for the different perception levels; to identity the SFs which live through the IMC life cycle phases, for each information source (structural, chronological, strategic and environmental); and to discuss SF subgroups according to each IMC’s nature. The research methodology used a “participant observation” type of strategy, at an existing IMC at the Orkut platform, in order to collect and extract agreement levels (high, moderate and low) on thirteen SF (focus, sense of community, technology, service, sociability, members, management, recognition, participation, leadership, reputation, reliability and sustainability), which are fundamental in the IMC’s course for success. The studies that address the holistic notion of IMC life and death are still scarce, thus, this thesis presents the IMC life cycle model (IMC-LCM), picturing the initial steps, of creation, growth, maturity and transformation or death of an existing IMC at the Orkut platform, which counts more than 1200 members to-day. This community was chosen for the adequacy to the adopted methodology. The research used the LimeSurvey software for the database construction, which generated a sample of 104 respondents. This allowed the perceptual mapping... (Complete abstract click electronic access below)

O presente estudo caracteriza-se como pesquisa descritiva e analítica, e buscou estudar o fenômeno das construções de relacionamentos sociais que ocorrem no ciberespaço, para compreender seus fundamentos em Comunidades Mediadas pela Internet (CMI) para, dessa forma, reconhecer as razões do sucesso e descrever o ciclo de vida dessas comunidades. Com o objetivo geral de identificar os fatores de atração e participação de membros em CMIs, distribuídos em seu ciclo de vida, a pesquisa teve como objetivos específicos: diferenciar atributos definidores e atributos de sucesso de CMIs; discutir associação e participação como Fatores de Sucesso (FS) em CMIs; descrever a natureza dos FS para os níveis de percepções; para cada fonte de informação (estrutural, temporal, estratégico e ambiental), identificar os FS que transcorrem pelas fases do Ciclo de Vida da CMI; e discutir subconjuntos de FS conforme a natureza de cada CMI. A metodologia de pesquisa utilizou uma estratégia do tipo “observação participante”, junto a uma CMI existente na plataforma Orkut, a fim de coletar e extrair graus de concordância (alta média e baixa), sobre treze FS (foco, senso comunitário, tecnologia, serviço, sociabilidade, membros, gestão, reconhecimento, participação, liderança, reputação, confiança e sustentabilidade), fundamentais na trajetória da CMI ao sucesso. Por serem ainda escassos os estudos que abordam a noção holística de vida e morte das CMI, esta tese apresenta o modelo de ciclo de vida das CMI (MCV-CMI), retratando as etapas iniciais, de criação, de crescimento, de maturidade e de transformação ou morte de uma CMI existente na plataforma Orkut, que conta hoje com mais de 1200 integrantes. Essa comunidade foi selecionada em função da adequação à metodologia adotada. A pesquisa utilizou o software LimeSurvey para a construção da base de dados, que resultou...
Keywords: Ciência da informação; Web 2.0; Redes sociais on-line; Comunidades Mediadas pela Internet (CMI); Informação e tecnologia da computação; Internet-Mediated Communities; Success Factors; Life Cycle; Web 2.0; Social Networks